A lithium ion secondary battery
Patent Information
- Application Number
- CN202611043713.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-13
- Publication Date
- 2026-10-13
AI Technical Summary
[0004]有鉴于此,本申请要解决的技术问题在于克服现有的锂离子二次电池在高功率使用条件下无法兼顾高温循环与针刺安全性的缺陷
本申请提供的锂离子二次电池,包括正极片和电解液,所述正极片包括正极集流体以及设置于所述正极集流体厚度方向的至少一侧表面上的正极活性层,所述正极活性层包括正极活性物质;所述正极活性物质包括磷酸锰铁锂材料和镍钴锰酸锂材料,以所述正极活性层的质量为基准计,所述正极活性层中Mn元素的质量含量为a%,满足:1.2≤a≤15;所述电解液包括磷酸三炔丙酯,以所述电解液的质量为基准计,所述磷酸三炔丙酯的质量含量为b%,满足:0.01≤b≤2;并且满足:1≤a/b≤500。
Smart Images

Figure SMS_2 
Figure SMS_3 
Figure SMS_4
Abstract
Description
Technical Field
[0001] This application relates to the field of battery technology, specifically to a lithium-ion secondary battery. Background Technology
[0002] Power tools typically require batteries capable of high-rate discharge to meet the demands of high-power use. The commonly used positive electrode material is lithium nickel manganese cobalt oxide (NCM). While this material boasts advantages such as a high voltage platform and large specific capacity, it suffers from poor thermal stability and a low decomposition temperature in the delithiation state. This exacerbates side reactions between the electrolyte and the positive electrode, leading to increased internal resistance, a significant decrease in high-temperature cycle life, and a susceptibility to internal short circuits during nail penetration testing. This can trigger localized high temperatures and rapidly induce the decomposition of the positive electrode material, releasing oxygen. The oxygen then reacts violently with the flammable electrolyte, causing a rapid accumulation of heat and ultimately resulting in a battery fire or explosion.
[0003] Therefore, developing lithium-ion secondary batteries that combine high power, long high-temperature cycle life, and good puncture safety has become a key technological bottleneck in the field of power tools. Summary of the Invention
[0004] In view of this, the technical problem to be solved by this application is to overcome the shortcomings of existing lithium-ion secondary batteries that cannot take into account both high-temperature cycling and needle penetration safety under high-power operation conditions.
[0005] To achieve the above objectives, this application adopts the following technical solution.
[0006] According to an embodiment of this application, a lithium-ion secondary battery is provided, comprising a positive electrode sheet and an electrolyte. The positive electrode sheet includes a positive current collector and a positive active layer disposed on at least one side surface of the positive current collector in the thickness direction. The positive active layer includes a positive active material. The positive active material includes lithium manganese iron phosphate and lithium nickel cobalt manganese oxide. Based on the mass of the positive active layer, the mass content of Mn element in the positive active layer is a%, satisfying: 1.2≤a≤15. The electrolyte includes propargyl phosphate. Based on the mass of the electrolyte, the mass content of propargyl phosphate is b%, satisfying: 0.01≤b≤2; and satisfying: 1≤a / b≤500.
[0007] Furthermore, in some alternative implementations, at least one of the following conditions is met: (1) 1.5 ≤ a ≤ 11.5; (2) 0.05 ≤ b ≤ 1.5; (3) 1.5≤a / b≤200.
[0008] In some optional embodiments, the average particle size of the lithium iron manganese phosphate material is denoted as D1 μm, and the average particle size of the lithium nickel cobalt manganese oxide material is denoted as D2 μm, satisfying at least one of the following conditions: (1) 0.05≤D1≤12; (2) 1≤D2≤8; (3) D1≤D2.
[0009] In some optional embodiments, the following is satisfied: 0.01≤b / D1≤15.
[0010] In some optional embodiments, at least one of the following conditions is satisfied: (1) The lithium nickel cobalt manganese oxide material comprises single crystal particles; (2) The chemical formula of the lithium nickel cobalt manganese oxide material is Li g Ni x Co y Mn z E h O2, where 0.9≤g<1.1, 0.5≤x<1, 0<y<0.45, 0<z<0.45, 0≤h<0.1, and E comprises at least one of Al, Zr, B, Y, Sr, W, Ti, and Nb elements; (3) The ratio of the mass content of iron element to manganese element in the lithium iron manganese phosphate material is e, satisfying: 0.2≤e≤2.
[0011] Further, in some optional embodiments, the following is satisfied: 0.6≤e≤1.1.
[0012] In some optional embodiments, the positive electrode sheet further comprises a safety coating, the safety coating is located between the positive electrode current collector and the positive electrode active layer, the thickness of the safety coating is denoted as m μm, satisfying: 1≤m≤10.
[0013] Further, in some optional embodiments, the safety coating comprises inorganic particles, and the inorganic particles comprise at least one of alumina, boehmite, magnesium oxide, titanium oxide, zirconium oxide, calcium oxide, barium titanate, zinc oxide, silicon oxide, cobalt oxide, aluminum nitride, boron nitride, iron phosphate, aluminum phosphate, iron metaphosphate, and aluminum metaphosphate.
[0014] In some optional embodiments, the electrolyte further comprises a first lithium salt, the first lithium salt comprises at least one of lithium difluorodioxalate phosphate, lithium difluorooxalatoborate, and lithium difluorophosphate; based on the mass of the electrolyte, the mass content of the first lithium salt is denoted as f%, satisfying: 0.01≤f≤3.
[0015] In some optional embodiments, the electrolyte further includes a second lithium salt, which includes lithium bis(fluorosulfonyl)imide; the mass content of the second lithium salt is denoted as r%, based on the mass of the electrolyte, and satisfies: 0.5 ≤ r ≤ 10.
[0016] In some alternative embodiments, the electrolyte further comprises vinylene carbonate, and the mass content of vinylene carbonate, denoted as j%, is based on the mass of the electrolyte and satisfies: 0.01≤j≤5.
[0017] Furthermore, in some alternative implementations, the following condition is satisfied: 0.1≤b+j≤5.
[0018] In some alternative embodiments, the electrolyte further comprises fluoroethylene carbonate, and the mass content of the fluoroethylene carbonate is denoted as k%, based on the mass of the electrolyte, satisfying: 4≤k≤20.
[0019] In some optional embodiments, the lithium-ion secondary battery includes a negative electrode sheet, the negative electrode sheet includes a negative current collector and a negative active layer disposed on at least one side surface of the negative current collector in the thickness direction, the negative active layer includes a negative active material, the negative active material includes silicon-carbon material; based on the mass of the negative active layer, the mass content of silicon element in the negative active layer is denoted as h%, satisfying: 1≤h≤30.
[0020] In some alternative embodiments, the sphericity of the silicon-carbon material is denoted as i, which satisfies: 0.3≤i≤0.9.
[0021] In some optional embodiments, the lithium-ion secondary battery includes a separator, the separator comprising a base film, a functional layer, and a binder layer, the functional layer being located on at least one surface of the base film, the functional layer being present on the surface of the base film facing the positive electrode, the binder layer being disposed on the surface of the functional layer away from the base film, and / or, the binder layer being located on the surface of the base film where the functional layer is not present; the functional layer includes a nitrogen-containing organic compound, the nitrogen-containing organic compound including at least one of melamine, melamine cyanurate, melamine thiocyanate, 2,4,6-tris(4-hydroxyphenyl)-1,3,5-triazine, 2-phenylpyrimidine-4-carboxaldehyde, 1,4,6-dihydroxy-2-phenylpyrimidine, 5,6-diamino-2-phenyl-pyrimidine-4-ol, 4,6-dimethyl-2-phenylpyrimidine, uracil, and cytosine.
[0022] The technical solution of this application has the following advantages: The lithium-ion secondary battery provided in this application includes a positive electrode sheet and an electrolyte. The positive electrode sheet includes a positive current collector and a positive active layer disposed on at least one side surface of the positive current collector in the thickness direction. The positive active layer includes a positive active material. The positive active material includes lithium manganese iron phosphate and lithium nickel cobalt manganese oxide. Based on the mass of the positive active layer, the mass content of Mn element in the positive active layer is a%, satisfying: 1.2≤a≤15. The electrolyte includes propargyl phosphate. Based on the mass of the electrolyte, the mass content of propargyl phosphate is b%, satisfying: 0.01≤b≤2; and satisfying: 1≤a / b≤500.
[0023] This application precisely captures Mn dissolved from the positive electrode by controlling the content of Mn in the positive electrode active layer, the content of propargyl phosphate in the electrolyte, and their ratio, utilizing the phosphate ions generated by propargyl phosphate. 2+ This maximizes the balance between the high voltage platform and the positive electrode structure / thermal stability, as well as the negative electrode interface stability, thereby ensuring that the battery can take into account rate performance, high temperature cycle performance, and needle penetration safety.
[0024] Additional aspects and advantages of the embodiments of this application will be described and shown in part in the following description, or illustrated by practice of the embodiments of this application. Detailed Implementation
[0025] The following embodiments are provided to better understand this application and are not limited to the preferred embodiments described herein. They do not constitute a limitation on the content and scope of protection of this application. Any product that is the same as or similar to this application, derived by anyone under the guidance of this application or by combining features of this application with other prior art, falls within the scope of protection of this application.
[0026] It should be noted in the description of this application that the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance. Furthermore, the technical features involved in the different embodiments of this application described below may be combined with each other as long as they do not conflict with each other.
[0027] To address the poor thermal stability of NCM, a solution has been designed to mix NCM with lithium manganese iron phosphate (LMFP). LMFP has an olivine-type structure and maintains high thermal stability even in the delithiation state. When LMFP is mixed with NCM, LMFP can surround NCM, suppressing the chain reaction of active materials under thermal runaway conditions, thereby improving the battery's needle penetration safety performance. However, this study found that because NCM has a higher charging voltage plateau than LMFP, when the battery charging voltage is high, the Mn in LMFP... 3+It readily undergoes a disproportionation reaction, producing soluble Mn. 2+ This exacerbates the dissolution of manganese from the positive electrode. The dissolved manganese ions deposit on the surface of the negative electrode, which damages the SEI film on the surface of the negative electrode, causing the SEI film to thicken or be repeatedly repaired, thereby increasing the internal resistance of the battery. Especially under high temperature cycling conditions, high temperature will further exacerbate the rate of manganese dissolution, leading to accelerated capacity decay and rapid decline in high temperature cycling performance of the battery.
[0028] To address the issue that battery systems combining LMFP and NCM cannot simultaneously achieve high power, high-temperature cycle performance, and needle penetration safety, this application proposes the following solution.
[0029] According to an embodiment of this application, a lithium-ion secondary battery is provided, comprising a positive electrode sheet and an electrolyte. The positive electrode sheet includes a positive current collector and a positive active layer disposed on at least one side surface of the positive current collector in the thickness direction. The positive active layer includes a positive active material, which includes lithium manganese iron phosphate and lithium nickel cobalt manganese oxide. Based on the mass of the positive active layer, the mass content of Mn element in the positive active layer is a%, satisfying: 1.2≤a≤15. The electrolyte includes propargyl phosphate, and based on the mass of the electrolyte, the mass content of propargyl phosphate is b%, satisfying: 0.01≤b≤2, 1≤a / b≤500.
[0030] This application employs a hybrid cathode of LMFP and NCM. By controlling the Mn content (a%) in the cathode active layer between 1.2% and 15%, it achieves a balance between high voltage advantage and structural / thermal stability, facilitating a dual balance between rate performance and high-temperature cycling performance. If the Mn content in the cathode active layer is too high, the probability of manganese dissolution under high temperature and high voltage increases, leading to decreased cathode structural and thermal stability, anode interface degradation, and accelerated electrolyte decomposition, thus affecting the battery's rate performance, high-temperature cycling performance, and safety performance. Conversely, if the Mn content in the cathode active layer is too low, the lattice compactness is too high, increasing lithium-ion solid-phase diffusion resistance and deteriorating power characteristics. Insufficient Mn content also lowers the operating voltage of the LMFP and reduces active sites, resulting in a significant decrease in the average discharge voltage and active material utilization rate of the hybrid system, failing to meet the capacity target of the hybrid design.
[0031] This study found that during battery charging and discharging, tripropenyl phosphate (TPP) in the electrolyte undergoes ester bond breakage and electrochemical decomposition, producing anions such as phosphate ions (e.g., PO4). 3- Anions such as phosphate can react with Mn dissolved from the positive electrode. 2+By combining through coordination bonds or electrostatic interactions, stable complexes (such as Mn-PO4) are formed, thereby reducing the free concentration of manganese in the electrolyte, inhibiting the deposition of manganese ions on the negative electrode surface, and blocking the path of manganese ions to damage the negative electrode SEI film.
[0032] Furthermore, this application controls the TPP content (b%) in the electrolyte to be between 0.01% and 2%, and adjusts the ratio (a / b) of the Mn element content in the positive electrode active layer to the TPP content in the electrolyte to be within the range of 1-500. This allows the electrolyte to contain a relatively sufficient amount of anions such as phosphate, which can improve the capture of Mn dissolved from the positive electrode. 2+ The efficiency is maximized to maintain a balance between the high voltage platform and the positive electrode structure / thermal stability, as well as the negative electrode interface stability, thereby taking into account the battery rate performance, high temperature cycle performance, and needle penetration safety.
[0033] If the TPP content in the electrolyte is too low or the a / b ratio is too high, it will be difficult to effectively suppress the dissolution of manganese from the positive electrode. This will not only lead to a decrease in the structural and thermal stability of the positive electrode, but also cause the interface of the negative electrode to deteriorate and the electrolyte decomposition rate to increase, ultimately affecting the rate performance, high-temperature cycle performance, and safety performance of the battery. Conversely, if the TPP content in the electrolyte is too high or the a / b ratio is too low, on the one hand, it will increase the viscosity of the electrolyte, which will reduce the degree of lithium salt dissociation and ion migration rate, and deteriorate the rate performance. On the other hand, it will also lead to an excessively thick solid electrolyte film on the surface of the positive and negative electrodes, resulting in a larger pressure drop in the later stages of cycling and faster capacity decay. Thirdly, TPP itself has limited electrochemical stability, and excessive TPP is prone to decomposition and gas generation in high-pressure and high-temperature environments, leading to an increase in internal gas pressure in the battery and an increase in safety risks.
[0034] Furthermore, in some embodiments, by controlling the mass content of Mn element in the positive electrode active layer between 1.5% and 11.5%, it is possible to ensure that the mixed positive electrode obtains a high average discharge voltage and active material utilization rate to achieve the capacity design target, while also controlling the probability of manganese dissolution under high temperature and high voltage to a low level, thereby further improving the rate performance, high temperature cycle performance and safety performance of the battery.
[0035] It should be noted that various methods can be used to control the Mn content (a%) in this application. For example, while maintaining the total mass and chemical composition of the positive electrode active material, the mass content (a%) of Mn in the positive electrode active layer can be adjusted by controlling the mass ratio of lithium manganese iron phosphate (LFP) to lithium nickel cobalt manganese oxide (LCO). Specifically, increasing the mass percentage of LFP increases the value of a%, while decreasing it decreases it. Furthermore, the mass content of Mn in the positive electrode active layer can also be adjusted by adding LFP with different Mn contents and / or LCO with different Mn contents.
[0036] In this application, the content of Mn element in the positive electrode active layer can be tested using inductively coupled plasma atomic emission spectrometry (ICP-AES). For example, the content of Mn element in the positive electrode active layer can be 1.2%, 1.5%, 2.0%, 2.5%, 3.0%, 4.0%, 5.0%, 6.0%, 7.0%, 8.0%, 9.5%, 11.5%, 13.0%, 15.0%, or a value within any two of the above ranges.
[0037] Furthermore, in some embodiments, by controlling the mass content of triargyl phosphate in the electrolyte to be between 0.05% and 1.5%, the electrolyte viscosity can be made suitable, and the thickness of the solid electrolyte film on the positive / negative electrode surface can be moderate, thereby further improving the rate performance, high-temperature cycle performance and safety performance of the battery.
[0038] It should be noted that the mass content of propargyl phosphate in the electrolyte can be obtained by gas chromatography-mass spectrometry (GC-MS). For example, the mass content of propargyl phosphate can be 0.01%, 0.02%, 0.05%, 0.08%, 0.10%, 0.20%, 0.30%, 0.50%, 0.80%, 1.00%, 1.20%, 1.50%, 1.70%, 1.85%, 2.00%, or values within any range of two of the above values.
[0039] Furthermore, in some embodiments, by controlling a / b between 1.5 and 200, the amount of phosphate generated in the electrolyte is proportional to the amount of Mn dissolved from the positive electrode. 2+ The amount of energy is optimally matched, thereby more effectively ensuring the multiple balance between the high voltage platform and the positive electrode structure / thermal stability, and the negative electrode interface stability, further improving the battery rate performance, high temperature cycle performance and needle penetration safety.
[0040] For example, the value of a / b can be 1, 1.5, 2, 5, 10, 20, 50, 100, 150, 200, 250, 300, 350, 400, 500, etc., or a value within the range of any two of the above values.
[0041] In some embodiments, by controlling the average particle size D1 of the lithium manganese iron phosphate material within the range of 0.05 μm to 12 μm, the migration path of lithium ions in the one-dimensional channel of lithium manganese iron phosphate can be shortened, accelerating the transport efficiency of lithium ions in the co-mixed cathode, thereby improving the rate capability and cycle performance of the battery. If D1 is too small, the specific surface area of the particles is too large, which not only makes processing difficult but also easily triggers side reactions; if D1 is too large, the lithium ion migration path is too long, resulting in a significant decrease in lithium ion transport efficiency. The lithium manganese iron phosphate material in this application is a secondary particle formed by the agglomeration of primary particles, and the average particle size of the lithium manganese iron phosphate material refers to the average particle size of the agglomerated secondary particles.
[0042] In some implementations, by controlling the average particle size D2 of the lithium nickel cobalt manganese oxide material within the range of 1μm-8μm, a suitable specific surface area can be ensured. This facilitates the rapid insertion and extraction of lithium ions and effectively reduces the dissolution of manganese ions during high-temperature cycling. If D2 is too small, the finer particles will increase the specific surface area, enhancing the thermodynamic driving force of surface reactions at high temperatures, thereby accelerating the dissolution of manganese ions and deteriorating the high-temperature cycling performance of the battery. If D2 is too large, the diffusion path of lithium ions within the particles will be prolonged, leading to a decrease in the rate performance of the battery.
[0043] In some implementations, by controlling D1 to be less than or equal to D2, it can be ensured that lithium manganese iron phosphate particles surround lithium nickel cobalt manganese oxide particles, forming a denser particle packing structure. On the one hand, this can effectively suppress the chain reaction of lithium nickel cobalt manganese oxide material under thermal runaway conditions, improving the battery's needle penetration safety. On the other hand, it also helps to improve the electrode compaction density and the continuity of the lithium-ion transport network, ensuring the battery's rate performance and cycle stability. If D1 > D2, since the one-dimensional ion channels of lithium manganese iron phosphate are not conducive to lithium-ion transport, excessively large particle sizes will further prolong the lithium-ion migration path and block the ion transport channels of surrounding lithium nickel cobalt manganese oxide, thus leading to a decrease in lithium-ion transport efficiency. At the same time, small-sized lithium nickel cobalt manganese oxide particles are more likely to undergo side reactions with the electrolyte due to their increased specific surface area, accelerating manganese dissolution, which in turn can cause short circuits within the battery, deteriorating high-temperature cycle performance and reducing needle penetration safety.
[0044] It should be noted that the test methods for D1 and D2 include: disassembling the battery after discharging it to 2.8V, removing the positive electrode sheet, immersing it in dimethyl carbonate (DMC) solvent for 12 hours, and then rinsing it with DMC solvent to remove the lithium salt adhering to the surface; using an argon ion milling machine to laser-cut the positive electrode sheet, observing it with a scanning electron microscope (SEM), and using energy dispersive X-ray spectroscopy (EDS) elemental analysis to distinguish between lithium nickel cobalt manganese oxide particles and lithium manganese iron phosphate particles; randomly selecting at least 10 lithium nickel cobalt manganese oxide particles and at least 10 lithium manganese iron phosphate particles, measuring the particle size of each particle (when the particle is a regular circle, take its diameter; when the particle is irregularly shaped, take the longest straight segment inside the particle as the particle size), and calculating the average value of the particle sizes of the two types of particles, which gives D1 and D2. For example, the value of D1 can be 0.05μm, 0.1μm, 0.2μm, 0.5μm, 1.0μm, 1.5μm, 2.0μm, 2.5μm, 3.0μm, 3.5μm, 4.0μm, 4.5μm, 5.0μm, 5.5μm, 6.0μm, 7.0μm, 8.0μm, 10.0μm, 12.0μm, or a value within the range of any two of the above values; the value of D2 can be 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm, 5.5μm, 6μm, 6.5μm, 7μm, 7.5μm, 8μm, or a value within the range of any two of the above values.
[0045] In some embodiments, by controlling the ratio b / D1 between the mass content b% of triargyl phosphate and the particle size D1 μm of the lithium manganese iron phosphate material to be between 0.01 and 15, a sufficiently large and adequate protective layer can be formed on the surface of the cathode material, effectively suppressing the dissolution of manganese ions, thereby further improving the high-temperature cycle performance of the battery. If b / D1 is too small, the relative content of triargyl phosphate is insufficient or the particle size of lithium manganese iron phosphate is too large, making it difficult to form a complete and dense protective layer on the surface of the cathode material, weakening the suppression effect on the dissolution of manganese ions, and limiting the improvement of high-temperature cycle performance; if b / D1 is too large, the relative content of triargyl phosphate is too high, resulting in an excessively thick protective layer and increased electrode interface resistance, which is detrimental to the rate capability and high-temperature cycle performance of the battery; or, if the particle size of lithium manganese iron phosphate is too small, this will exacerbate the side reactions between the active material and the electrolyte, leading to a decrease in the stability of the cathode interface, and thus reducing the needle penetration safety.
[0046] For example, the value of b / D1 can be 0.01, 0.05, 0.1, 0.2, 0.5, 1, 1.5, 2, 3, 4, 5, 6, 8, 10, 12, 15, etc., or a value within the range of any two of the above values.
[0047] In some embodiments, the lithium nickel cobalt manganese oxide material comprises single crystal particles. The lithium nickel cobalt manganese oxide material with a single crystal structure has high mechanical strength and thermal stability, can maintain structural integrity at high temperatures, thereby inhibiting the fragmentation of the material under abuse conditions such as nail penetration, reducing the risk of internal short circuits, and further improving the nail penetration safety performance of the battery.
[0048] The term "single crystal particle" means that the particle is composed of a single crystal, the entire particle has a continuous, uninterrupted crystal structure, and no grain boundaries exist. Grain boundaries are defect regions in the crystal structure with irregular atomic arrangements, which easily become the starting point for crack initiation and propagation under the action of high temperature or mechanical stress, and become the preferred site for side reactions. Since single crystal particles have no grain boundaries, they can effectively inhibit the fragmentation and pulverization of particles under high-temperature charge-discharge or nail penetration abuse conditions, maintain the structural integrity of the positive electrode material, reduce the risk of fresh surface exposure and internal short circuit caused by particle breakage, thereby significantly improving the nail penetration safety performance of the battery.
[0049] In some embodiments, the chemical formula of the lithium nickel cobalt manganese oxide material is Li g Ni x Co y Mn z E h O2, where 0.9≤g<1.1, 0.5≤x<1, 0<y<0.45, 0<z<0.45, 0≤h<0.1, and E includes at least one of the elements Al, Zr, B, Y, Sr, W, Ti, and Nb.
[0050] To further improve the nail penetration safety performance of the battery, in some embodiments, the present application controls the value of e, which is the ratio of the mass content of iron element to manganese element in the lithium iron manganese phosphate material, within the range of 0.2-2, because Fe 2+ can increase the redox potential of Mn³ + / Mn² + , making Mn³ + more difficult to be reduced to Mn² in the later stage of discharge + , thereby improving the chemical stability of the positive electrode active material, and alleviating the Jahn-Teller distortion, so as to stabilize the crystal structure of lithium iron manganese phosphate, making it not easy to break or pulverize during the nail penetration test, further reducing the probability of internal short circuit and lowering the risk of thermal runaway. In particular, when the value of e is between 0.6 and 1.1, the molar content ratio of iron element to manganese element is more balanced, which can maximally inhibit the Jahn-Teller distortion, keep the crystal structure of lithium iron manganese phosphate intact during the nail penetration process, further reduce the risk of positive electrode material breakage and internal short circuit, thereby significantly improving the nail penetration safety performance of the battery Understandably, the term "Jahn-Teller distortion" refers to the distortion of Mn in lithium manganese iron phosphate materials. 3+ The asymmetry of the electronic structure of ions causes distortion of the octahedral coordination field, resulting in a twisted crystal structure. This distortion reduces the structural stability of the material and easily leads to the accumulation of lattice stress during cycling, resulting in particle breakage and accelerated dissolution of manganese ions. Introducing an appropriate amount of Fe... 2+ It can alleviate Mn 3+ The resulting Jahn-Teller distortion stabilizes the crystal structure.
[0051] It should be noted that the mass content of iron and manganese in lithium manganese iron phosphate materials can be obtained by inductively coupled plasma atomic emission spectrometry (ICP-AES). The value of e can be obtained by dividing the measured mass content of iron and manganese by the mass content of manganese. For example, the value of e can be 0.2, 0.3, 0.5, 0.6, 0.8, 0.9, 1.0, 1.1, 1.2, 1.4, 1.5, 1.6, 1.7, 1.9, 2.0, etc., or a value within any range of two of the above values.
[0052] Under abusive conditions such as needle penetration, the positive electrode material decomposes and releases oxygen at localized high temperatures. If the heat generated is rapidly transmitted to the current collector, it will exacerbate heat accumulation and lead to thermal runaway. Simultaneously, the internal short circuit formed by the direct contact of the positive and negative electrodes will instantly release a large amount of heat, causing the battery to catch fire and explode. Therefore, in some embodiments, the positive electrode sheet in this application also includes a safety coating located between the positive electrode current collector and the positive electrode active layer. By controlling the thickness of the safety coating between 1μm and 10μm, the safety coating can effectively block heat transfer between the positive electrode material and the current collector, slowing down the rate at which heat generated by the positive electrode material propagates to the current collector, and reducing safety hazards caused by heat accumulation. Furthermore, under abusive conditions such as needle penetration, this safety coating can effectively prevent short circuits caused by direct contact between the positive and negative electrodes, preventing the generation of a large amount of heat inside the battery and thus preventing thermal runaway, thereby significantly improving the battery's needle penetration safety performance.
[0053] It should be noted that the testing method for the thickness of the safety coating includes: discharging the battery to 2.8 V and then disassembling it, removing the positive electrode sheet, immersing it in DMC solvent for 12 hours, and then rinsing it with DMC solvent to remove the lithium salt adhering to the surface of the positive electrode sheet; using an argon ion milling machine to laser-cut the positive electrode sheet, observing the cut cross-section using a scanning electron microscope (SEM), and randomly selecting 5 locations to measure the thickness of the safety coating, calculating the average value. For example, the thickness of the safety coating can be 1.0 μm, 1.5 μm, 2.0 μm, 2.5 μm, 3.0 μm, 3.5 μm, 4.0 μm, 5.0 μm, 5.5 μm, 6.0 μm, 7.0 μm, 7.5 μm, 8.0 μm, 9.0 μm, 10.0 μm, or a value within any two of the above ranges.
[0054] Furthermore, in some embodiments, the safety coating comprises inorganic particles, including at least one of alumina, boehmite, magnesium oxide, titanium oxide, zirconium oxide, calcium oxide, barium titanate, zinc oxide, silicon oxide, cobalt oxide, aluminum nitride, boron nitride, iron phosphate, aluminum phosphate, iron metaphosphate, and aluminum metaphosphate. The safety coating containing the above substances can block the rapid transfer of heat and physically isolate the positive and negative electrodes during needle penetration, thereby significantly improving the needle penetration safety performance of the battery.
[0055] In some embodiments, the electrolyte further includes a first lithium salt, which includes at least one of lithium difluorodioxalate phosphate (LiDFOP), lithium difluorooxalate borate (LiODFB), and lithium difluorophosphate (LiPO2F2). By controlling the mass content f% of the first lithium salt in the electrolyte to be between 0.01% and 3%, the first lithium salt can form a low-resistivity interface film on the negative electrode surface, thereby improving the transport efficiency of lithium ions at the negative electrode interface.
[0056] It should be noted that the mass content of the first lithium salt can be obtained by testing with an ion chromatograph (IC). For example, the mass content of the first lithium salt can be 0.01%, 0.02%, 0.05%, 0.1%, 0.2%, 0.3%, 0.5%, 0.7%, 1.0%, 1.2%, 1.5%, 1.7%, 2.0%, 2.2%, 2.5%, 2.7%, 2.9%, 3.0%, or a value within any two of the above ranges.
[0057] In some embodiments, the electrolyte further includes a second lithium salt, which includes lithium bis(fluorosulfonyl)imide. By controlling the mass content (r%) of the second lithium salt in the electrolyte to be between 0.5% and 10%, the lithium ion concentration in the electrolyte can be increased, prompting free solvent molecules and lithium salt anions to jointly participate in the formation of a solvation structure. This reduces the oxidative decomposition of free solvent molecules on the positive electrode surface, thereby reducing the dissolution of manganese ions from the positive electrode. Simultaneously, when lithium ions migrate to the electrode surface, the concentration of lithium salt anions in the solvation structure increases on the electrode surface. Due to their higher reduction potential than solvent molecules, they form a LiF-rich inorganic protective film on the electrode surface. This protective film can reduce the interfacial resistance of lithium ions crossing the electrode surface and effectively prevent direct contact between the electrolyte and the positive electrode material, further inhibiting the dissolution of manganese ions and the oxidative decomposition of the electrolyte, thereby improving the cycle stability of the battery.
[0058] It should be noted that the mass content of the second lithium salt can be obtained by ion chromatography (IC). For example, the mass content of the second lithium salt can be 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 4.0%, 5.0%, 6.0%, 7.0%, 8.0%, 9.0%, 10.0%, or a value within any two of the above ranges.
[0059] In some embodiments, the electrolyte further comprises vinylene carbonate. Based on the mass of the electrolyte, by controlling the mass content (j%) of vinylene carbonate between 0.01% and 5%, the vinylene carbonate can participate in the formation of an organic-inorganic composite film on the electrode surface. This imparts high flexibility to the SEI film, allowing it to adapt to the volume expansion of the silicon anode without rupture, suppressing side reactions caused by direct contact between the electrolyte and the electrode, and thus improving the battery's cycle performance. If j% is too low, the vinylene carbonate content is insufficient, resulting in inadequate SEI film flexibility, making it difficult to adapt to the expansion of the silicon anode, easily leading to SEI film rupture and triggering side reactions. If j% is too high, there is an excess of vinylene carbonate, resulting in an excessively thick or highly impedance SEI film, hindering lithium-ion transport and degrading cycle performance.
[0060] It should be noted that the mass content of vinylene carbonate can be obtained by gas chromatography-mass spectrometry (GC-MS). For example, the mass content of vinylene carbonate can be 0.01%, 0.02%, 0.05%, 0.10%, 0.20%, 0.50%, 1.00%, 1.50%, 2.00%, 2.50%, 3.00%, 3.50%, 4.00%, 4.50%, 5.00%, or values within any range of two of the above values.
[0061] In some embodiments, the electrolyte further comprises fluoroethylene carbonate. Based on the mass of the electrolyte, by controlling the mass content (k%) of fluoroethylene carbonate to be between 4% and 20%, the fluoroethylene carbonate can participate in the formation of an organic-inorganic composite film on the electrode surface, giving the SEI film higher mechanical strength, thereby effectively resisting the stress generated by the expansion of the silicon anode, maintaining the integrity of the SEI film, further suppressing side reactions, and improving the cycle performance of the battery.
[0062] It should be noted that the mass content of fluoroethylene carbonate can be obtained by gas chromatography-mass spectrometry (GC-MS). For example, the mass content of fluoroethylene carbonate can be 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 18%, 20%, or a value within any two of the above ranges.
[0063] Since both propargyl phosphate and vinylene carbonate participate in the formation of interfacial films on the electrode surface, thereby increasing the interfacial impedance to some extent, the sum of their contents needs to be controlled within an appropriate range. If the total content of both is too low, it will be difficult to form a sufficiently dense protective film on the positive and negative electrode surfaces, and side reactions cannot be effectively suppressed; if the total content of both is too high, the interfacial impedance will increase excessively, which will significantly reduce the lithium-ion transport efficiency and thus degrade the cycle performance of the battery.
[0064] Based on this, in some embodiments, this application controls the sum of the mass content b% of triargyl phosphate and the mass content j% of vinylene carbonate, b+j, to be between 0.1% and 5%, which can ensure that the electrode obtains sufficient interface protection while avoiding excessive increase in interface impedance, thereby maintaining good lithium-ion transport characteristics and cycle stability.
[0065] For example, the value of b+j can be 0.1%, 0.3%, 0.5%, 0.7%, 1.0%, 1.3%, 1.6%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 4.8%, 5.0%, etc., or a value within the range of any two of the above values.
[0066] In high-power applications, the lithium-ion insertion rate at the negative electrode needs to match the extraction rate at the positive electrode. If the lithium insertion potential of the negative electrode material is too low, lithium ions cannot be inserted in time and tend to deposit on the negative electrode surface, forming lithium dendrites. This also consumes active lithium ions, leading to a decrease in battery capacity and a shortened lifespan. Silicon-carbon materials have a higher lithium insertion potential than graphite materials, making them more suitable for high-power applications. However, the volume change rate of silicon-carbon materials during cycling is much higher than that of graphite materials, making them prone to stress concentration and structural damage to the negative electrode material, resulting in a decrease in battery cycle performance.
[0067] Therefore, in some embodiments, the lithium-ion secondary battery includes a negative electrode sheet, the negative electrode sheet includes a negative current collector and a negative electrode active layer disposed on at least one side surface of the negative current collector in the thickness direction, the negative electrode active layer includes a negative electrode active material, the negative electrode active material includes silicon-carbon material; based on the mass of the negative electrode active layer, the mass content of silicon element in the negative electrode active layer is denoted as h%. By controlling the mass content of silicon element within the range of 1%-30%, the negative electrode can obtain the high power adaptability brought by the high lithium intercalation potential of silicon-carbon material, while controlling the volume expansion of silicon-carbon material within an acceptable range, reducing the structural damage and stress concentration of the negative electrode material caused by excessive volume change rate, thereby maintaining the cycle stability of the battery while ensuring high-power usage scenarios.
[0068] It should be noted that the mass content of silicon can be obtained by testing with a thermogravimetric analyzer (such as a TGA 550 thermogravimetric analyzer). For example, the mass content of silicon can be 1%, 3%, 5%, 7%, 9%, 11%, 13%, 15%, 17%, 19%, 21%, 23%, 25%, 28%, 30%, or a value within any two of the above ranges.
[0069] In some implementations, by controlling the sphericity of silicon-carbon particles within the range of 0.3-0.9, the silicon-carbon material can have a low sphericity, thereby forming a rich porous structure. This facilitates the uniform dispersion and filling of the conductive agent, improves the wettability of the electrolyte to the negative electrode and the lithium-ion transport efficiency, and simultaneously reserves space for the volume expansion of the silicon-carbon material, maintaining the structural integrity of the negative electrode material and further improving the cycle stability of the battery. If the sphericity of the silicon-carbon particles is too large, the porosity between particles decreases, making it difficult to effectively buffer the stress generated by volume expansion, leading to stress concentration and making cracks more likely to form. This, in turn, damages the structural integrity of the negative electrode and reduces cycle stability.
[0070] It should be noted that the test method for the sphericity of silicon-carbon particles includes: discharging the battery to 2.8 V and then disassembling it, removing the negative electrode sheet, immersing it in dimethyl carbonate (DMC) solvent for 12 hours, rinsing it with DMC solvent to remove lithium salt adhering to the surface of the negative electrode sheet, drying it, preparing a sample, and obtaining scanning electron microscope (SEM) images of the silicon-based material in the negative electrode sheet; importing the obtained SEM images into image processing software (such as ImageJ) with particle recognition and analysis functions, using the software's particle analysis function to automatically identify the silicon-carbon particles in the image, and calculating the sphericity of each silicon-carbon particle. For example, the sphericity of silicon-carbon particles can be 0.30, 0.35, 0.40, 0.45, 0.50, 0.55, 0.60, 0.65, 0.70, 0.75, 0.80, 0.85, 0.90, or values within any two of the above ranges.
[0071] In some embodiments, the lithium-ion secondary battery includes a separator comprising a base film, a functional layer, and a binder layer. The functional layer is located on at least one surface of the base film, and the functional layer is present on the surface of the base film facing the positive electrode. The binder layer is disposed on the surface of the functional layer away from the base film, and / or, the binder layer is located on the surface of the base film where the functional layer is not present. In this separator structure, the functional layer has high thermal stability and mechanical strength, maintaining effective isolation between the positive and negative electrodes; the binder layer enhances the bonding force between the layers and provides additional physical isolation protection. Under abuse conditions such as needle penetration, this multilayer structure can effectively prevent internal short circuits caused by direct contact between the positive and negative electrodes, reducing the risk of local heat accumulation and thermal runaway, thereby significantly improving the battery's needle penetration safety performance.
[0072] The functional layer includes nitrogen-containing organic compounds, including at least one of melamine, melamine cyanurate, melamine thiocyanate, 2,4,6-tris(4-hydroxyphenyl)-1,3,5-triazine, 2-phenylpyrimidine-4-carboxaldehyde, 1,4,6-dihydroxy-2-phenylpyrimidine, 5,6-diamino-2-phenyl-pyrimidine-4-ol, 4,6-dimethyl-2-phenylpyrimidine, uracil, and cytosine.
[0073] The nitrogen-containing functional groups in the aforementioned nitrogen-containing organic compounds can form hydrogen bonds or covalent bonds with hydroxyl or carboxyl groups on the surface of the base film, thereby enabling the functional layer to adhere tightly to the surface of the base film. At the same time, the functional layer has high thermal stability and can suppress thermal shrinkage and melting of the base film at high temperatures, maintain effective isolation between the positive and negative electrodes, and avoid thermal runaway caused by short circuits during nail penetration testing, thereby further improving the nail penetration safety performance of the battery.
[0074] The present application will be further described in detail below with reference to specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in this application. Where specific experimental steps or conditions are not specified in the embodiments and comparative examples, they can be performed according to the conventional experimental steps or conditions described in the literature in the art. Reagents or instruments used, unless otherwise specified, are all commercially available conventional reagent products.
[0075] Example 1 This embodiment provides a method for preparing a lithium-ion secondary battery, including the following steps: Step 1: Preparation of the positive electrode sheet Boehmite, carbon black, polyacrylate, and N-methylpyrrolidone (NMP) were mixed, and the slurry solids content was adjusted to 40%. After thorough stirring, a safety coating slurry was obtained; the mass ratio of boehmite, carbon black, and polyacrylate was 85:5:10. The safety coating slurry was then applied to the upper and lower surfaces of an aluminum foil using a gravure roller, and after drying, a safety coating with a thickness of 5 μm was obtained.
[0076] Lithium nickel cobalt manganese oxide material (chemical formula LiNi) 0.9 Co 0.05 Mn 0.05 O2 (average particle size 4 μm), lithium manganese iron phosphate (iron to manganese mass ratio 0.85, average particle size 6.5 μm), polyvinylidene fluoride (PVDF), carbon black, and carbon nanotubes (CNT) were mixed in a mass ratio of 63.3:32.7:2:1.5:0.5. NMP was added to adjust the solid content of the slurry to 75%. The mixture was stirred under vacuum until it became a homogeneous and fluid positive electrode active slurry. This positive electrode active slurry was uniformly coated onto both surfaces of an aluminum foil with a safety coating, then dried, rolled, and slit to obtain the positive electrode sheet.
[0077] Step 2: Preparation of the negative electrode Artificial graphite, silicon carbide (sphericity 0.7), sodium carboxymethyl cellulose (CMC-Na), styrene-butadiene rubber, conductive carbon black (SP), and single-walled carbon nanotubes (SWCNTs) were mixed in a mass ratio of 60:34.5:2.5:1.5:1:0.5. Deionized water was added, and the mixture was stirred evenly under vacuum to obtain a negative electrode active slurry. The negative electrode active slurry was uniformly coated on both surfaces of a copper foil, dried at room temperature, and then transferred to an 80°C oven for drying for 10 hours. The foil was then subjected to cold pressing, slitting, cleaning, and sheet forming to obtain the negative electrode sheet.
[0078] Step 3: Preparation of electrolyte In an argon-filled glove box with a water content below 0.1 ppm and an oxygen content below 0.1 ppm, ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) were uniformly mixed in a volume ratio of 3:6:1. Then, 7% (based on the total mass of the electrolyte) of fully dried lithium hexafluorophosphate and 5% (based on the total mass of lithium difluorosulfonyl imide) were added. After dissolution, 0.5% (based on the total mass of the electrolyte) of propargyl phosphate, 0.5% of LiPO₂F₂, 0.3% of LiODFB, 1% of vinylene carbonate, and 5% of fluoroethylene carbonate were added. After thorough stirring, the electrolyte was prepared after testing and confirming that the moisture and free acid content were within acceptable limits.
[0079] Step 4: Preparation of lithium-ion secondary batteries The positive electrode sheet obtained in the first step, the negative electrode sheet obtained in the second step, and the separator are stacked and wound in the order of positive electrode sheet, separator, and negative electrode sheet to obtain a battery cell. The battery cell is placed in an outer packaging aluminum foil, and the electrolyte obtained in the third step is injected. Then, it undergoes vacuum sealing, settling, formation, shaping, and sorting processes to obtain a lithium-ion secondary battery. The separator includes a base film (polypropylene), a functional layer (including melamine cyanurate), and a binder layer (including polymethyl methacrylate particles). The functional layer is located on one side of the base film, and the binder layer is located on the side of the functional layer away from the base film and on the surface of the base film where the functional layer is not located.
[0080] The charging and discharging voltage range of the battery in this application is 2.5 V-4.2 V.
[0081] The preparation methods of Examples 2-24 are basically the same as those of Example 1, with the differences shown in Tables 1-2. The Mn content in the positive electrode active layer is adjusted by regulating the ratio of lithium nickel cobalt manganese oxide to lithium manganese iron phosphate and / or by adjusting the chemical composition of the lithium nickel cobalt manganese oxide and lithium manganese iron phosphate materials.
[0082] Example 25 The difference between this embodiment and Embodiment 1 lies in the composition of the diaphragm. In this embodiment, the melamine cyanurate in the diaphragm functional layer is replaced with aluminum oxide, while the rest is the same as in Embodiment 1.
[0083] The preparation methods of Comparative Examples 1-6 are basically the same as those of Example 1. The differences are shown in Tables 1-2.
[0084] In Tables 1-2, " "This means that the parameter values are the same as in Example 1, but it does not exclude the possibility of reasonably foreseeable errors such as test errors."
[0085] Table 1
[0086] Table 2
[0087] Test case 1. Cyclic performance test Place the battery in an environment of 55±3℃, first discharge it to 2.5V with a current of 0.5C, then charge it to 4.2V with a constant current of 2C, then charge it to 0.05C with a constant voltage at 4.2V, let it stand for 5 minutes, and then discharge it to 2.5V with a constant current of 5C. This is one charge-discharge cycle. Record the discharge capacity of the first cycle as Q1 mAh and the discharge capacity of the Nth cycle as Q2 mAh. Calculate the capacity retention rate of the Nth cycle R = Q2 / Q1 × 100%, and record the capacity retention rate of the battery after 500 cycles.
[0088] 2. Needle puncture safety performance test The battery was placed in an environment of 25±3℃. First, it was discharged to the lower limit voltage using a 0.5C current and allowed to stand for 10 minutes. Then, it was charged at a constant current of 0.7C to the upper limit voltage of 4.2V, followed by constant voltage charging until the current cutoff was 0.02C. After standing for 10 minutes, it was discharged to the lower limit voltage using a 1C current. This constituted one charge-discharge cycle. After 5 charge-discharge cycles, the battery was charged at a constant current of 0.7C to the upper limit voltage of 4.2V, followed by constant voltage charging until the current cutoff was 0.02C. After standing for 10 minutes, at 25℃, a 3mm diameter, 15mm tip nail was driven through the center of the cell at a speed of 30m / s. The nail remained inside the battery for 5 minutes. If the battery did not smoke, catch fire, or explode during the test, it was considered to have passed. 30 batteries were tested in each group, and the pass rate of the nail penetration test was recorded.
[0089] 3. Ratio Performance Test At 25±3℃, the battery was charged at a constant current of 0.7C to 4.2V, then charged at a constant voltage of 0.025C to the cutoff current, and allowed to stand for 5 minutes. Then, it was discharged at a constant current of 0.2C to 2.5V, and the discharge capacity at this point was recorded as the initial capacity. Subsequently, the battery was charged at a constant current of 0.7C to 4.2V, then charged at a constant voltage of 0.025C to the cutoff current, and allowed to stand for 5 minutes. Finally, it was discharged at a constant current of 2.5C to 2.5V, and the discharge capacity at this point was recorded as the 2.5C discharge capacity. The rate performance was calculated using the following formula: Rate performance (%) = (2.5C discharge capacity / Initial capacity) × 100%.
[0090] The test results are shown in Table 3.
[0091] Table 3
[0092] As can be seen from Tables 1-3, this application, by controlling the content of Mn in the positive electrode active layer, the content of propargyl phosphate in the electrolyte, and their ratio, utilizes the phosphate ions generated by the decomposition of propargyl phosphate to accurately capture the Mn dissolved from the positive electrode. 2+ To maintain a balance between high voltage platform, positive electrode structure / thermal stability and negative electrode interface stability, the battery can achieve a balance between rate performance, high temperature cycle performance and needle penetration safety.
[0093] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.
Claims
1. A lithium-ion secondary battery, comprising a positive electrode and an electrolyte, wherein the positive electrode comprises a positive current collector and a positive active layer disposed on at least one surface of the positive current collector in the thickness direction, the positive active layer comprising a positive active material; characterized in that, The positive electrode active material includes lithium manganese iron phosphate material and lithium nickel cobalt manganese oxide material. Based on the mass of the positive electrode active layer, the mass content of Mn element in the positive electrode active layer is a%, which satisfies: 1.2≤a≤15. The electrolyte includes propargyl phosphate, and the mass content of propargyl phosphate is b% based on the mass of the electrolyte, satisfying: 0.01≤b≤2. And it satisfies: 1≤a / b≤500.
2. The lithium-ion secondary battery according to claim 1, characterized in that, At least one of the following conditions must be met: (1)1.5≤a≤11.5; (2)0.05≤b≤1.5; (3) 1.5≤a / b≤200.
3. The lithium-ion secondary battery according to claim 1, characterized in that, The average particle size of the lithium manganese iron phosphate material is denoted as D1 μm, and the average particle size of the lithium nickel cobalt manganese oxide material is denoted as D2 μm, satisfying at least one of the following conditions: (1)0.05≤D1≤12; (2)1≤D2≤8; (3) D1≤D2.
4. The lithium-ion secondary battery according to claim 3, characterized in that, It satisfies: 0.01≤b / D1≤15.
5. The lithium-ion secondary battery according to any one of claims 1-4, characterized in that, At least one of the following conditions must be met: (1) The lithium nickel cobalt manganese oxide material comprises single crystal particles; (2) The chemical formula of the lithium nickel cobalt manganese oxide material is Li g Ni x Co y Mn z E h O2, where 0.9≤g<1.1, 0.5≤x<1, 0<y<0.45, 0<z<0.45, 0≤h<0.1, and E includes at least one of the elements Al, Zr, B, Y, Sr, W, Ti, and Nb; (3) The mass ratio of iron to manganese in the lithium manganese phosphate material is e, which satisfies: 0.2≤e≤2, preferably 0.6≤e≤1.
1.
6. The lithium-ion secondary battery according to any one of claims 1-4, wherein the positive electrode further comprises a safety coating, the safety coating being located between the positive electrode current collector and the positive electrode active layer, and the thickness of the safety coating being denoted as m μm, satisfying: 1≤m≤10; Preferably, the safety coating comprises inorganic particles, which include at least one of alumina, boehmite, magnesium oxide, titanium oxide, zirconium oxide, calcium oxide, barium titanate, zinc oxide, silicon oxide, cobalt oxide, aluminum nitride, boron nitride, iron phosphate, aluminum phosphate, iron metaphosphate, and aluminum metaphosphate.
7. The lithium-ion secondary battery according to any one of claims 1-4, characterized in that, At least one of the following conditions must be met: (1) The electrolyte further includes a first lithium salt, which includes at least one of lithium difluorooxalate phosphate, lithium difluorooxalate borate, and lithium difluorophosphate; the mass content of the first lithium salt is denoted as f%, based on the mass of the electrolyte, and satisfies: 0.01≤f≤3; (2) The electrolyte further includes a second lithium salt, which includes lithium difluorosulfonylimide; the mass content of the second lithium salt is denoted as r% based on the mass of the electrolyte, satisfying: 0.5≤r≤10; (3) The electrolyte also contains vinylene carbonate. Based on the mass of the electrolyte, the mass content of vinylene carbonate is denoted as j%, which satisfies: 0.01≤j≤5. (4) The electrolyte also contains fluoroethylene carbonate. The mass content of the fluoroethylene carbonate is denoted as k%, based on the mass of the electrolyte, and satisfies: 4≤k≤20.
8. The lithium-ion secondary battery according to claim 7, characterized in that, It satisfies: 0.1≤b+j≤5.
9. The lithium-ion secondary battery according to any one of claims 1-4, wherein the lithium-ion secondary battery comprises a negative electrode sheet, the negative electrode sheet comprises a negative electrode current collector and a negative electrode active layer disposed on at least one side surface of the negative electrode current collector in the thickness direction, the negative electrode active layer comprises a negative electrode active material, and the negative electrode active material comprises a silicon-carbon material. Based on the mass of the negative electrode active layer, the mass content of silicon in the negative electrode active layer is denoted as h%, which satisfies: 1≤h≤30; And / or, the sphericity of the silicon-carbon material is denoted as i, which satisfies: 0.3≤i≤0.
9.
10. The lithium-ion secondary battery according to any one of claims 1-4, characterized in that, The lithium-ion secondary battery includes a separator, which includes a base film, a functional layer, and a binder layer. The functional layer is located on at least one side surface of the base film, and the functional layer is located on the side surface of the base film facing the positive electrode. The binder layer is disposed on the side surface of the functional layer away from the base film, and / or the binder layer is located on the surface of the base film where the functional layer is not provided. The functional layer includes nitrogen-containing organic compounds, including at least one of melamine, melamine cyanurate, melamine thiocyanate, 2,4,6-tris(4-hydroxyphenyl)-1,3,5-triazine, 2-phenylpyrimidine-4-carboxaldehyde, 1,4,6-dihydroxy-2-phenylpyrimidine, 5,6-diamino-2-phenyl-pyrimidine-4-ol, 4,6-dimethyl-2-phenylpyrimidine, uracil, and cytosine.